PENGARUH PEMBERIAN ZAT MULTI GIZI MIKRO DAN PENDIDIKAN GIZI TERHADAP PENGETAHUAN GIZI, PEMENUHAN ZAT GIZI DAN STATUS BESI REMAJA PUTRI - Cesilia Meti Dwiriani; Rimbawan Rimbawan; Hardinsyah Hardinsyah; Hadi Riyadi; Drajat Martianto (Food and Nutrition Society of Indonesia, 2011)
This study was aimed to analyze the effect of multi-micronutrients (MMN) supplementation and nutrition education on nutrition knowledge, mean adequacy ratio (MAR) and iron status of young adolescent girls (YAG). The study was done in three purposively selected junior high schools (JHS) in rural Bogor by implementing a quasi experiment control trial for 112 YAG for 16 weeks: thirty five YAG in the first JHS as a MMN group (SG) were given three times of MMN tablets per week, forty two YAG in the second JHS were given MMN tablet plus nutrition education delivered by trained teacher fortnightly called SGP group and thirty five YAG in the third JHS as a control group. The result showed that the increment of nutrition knowledge score as well as MAR of SGP group were significantly higher than the other two groups. The decrement level of hemoglobin (Hb) in SG and SGP groups was significantly lower than in control group, but in the subset data of anemic group, both intervention groups had significantly increased level of Hb. This imply that nutrition education improved nutrition knowledge of YAG, but MMN tablet could not improve Hb level in general and only had effect on YAG suffering from anemia.Key words: multi-micro nutrients, nutrition education, iron status, adolescent girls